Applying sentinel event reviews to policing - Hollway, John F. (Criminology & public policy, 2019)
A sentinel event review (SER) is a system‐based, multistakeholder review of an organizational error. The goal of an SER is to prevent similar errors from recurring in the future rather than identifying and punishing the responsible parties. In this article, we provide a detailed description of one of the first SERs conducted in an American police department—the review of the Lex Street Massacre investigation and prosecution, which resulted in the wrongful incarceration of four innocent men for 18 months. The results of the review suggest that SERs may help identify new systemic reforms for participating police departments and other criminal justice agencies.